Clean Energy Reform: The Correlation Between Carbon Tax on Production Costs and Emissions of Power Plants - Dwinta Mulyanti; Rofily Putriyandari; Abdul Rohman; Novi Nurcahyani (Pattimura University, 2026)
This study examines the relationship between carbon tax payments, electricity production costs, and carbon emission indicators in coal-fired power plants (PLTU) in Indonesia following the implementation of the carbon tax policy in 2022. Using post-implementation operational data, this study applies a descriptive and associative quantitative approach, acknowledging the potential endogeneity and mechanical relationships embedded in emission-based fiscal variables. The results indicate that carbon tax payments are not significantly associated with electricity production costs, suggesting that cost structures remain dominated by coal prices and operational efficiency. In contrast, a strong positive association is observed between carbon tax payments and carbon emission intensity, reflecting the mechanical linkage between emission-based taxes and emission indicators rather than policy effectiveness. These findings imply that the current carbon tax in Indonesia functions primarily as a fiscal and emission-reporting instrument, rather than an effective environmental control mechanism. The study highlights the need for complementary policies, technological upgrades, and more robust empirical designs to properly evaluate the environmental effectiveness of carbon taxation